Calorie restriction alleviates the age‐related decrease in neural progenitor cell division in the aging brain. Issue 12 (16th June 2013) - Park, June‐Hee; Glass, Zachary; Sayed, Kasim; Michurina, Tatyana V.; Lazutkin, Alexander; Mineyeva, Olga; Velmeshev, Dmitry; Ward, Walter F.; Richardson, Arlan; Enikolopov, Grigori
Abstract Production of new neurons from stem cells is important for cognitive function, and the reduction of neurogenesis in the aging brain may contribute to the accumulation of age‐related cognitive deficits. Restriction of calorie intake and prolonged treatment with rapamycin have been shown to extend the lifespan of animals and delay the onset of the age‐related decline in tissue and organ function. Using a reporter line in which neural stem and progenitor cells are marked by the expression of green fluorescent protein (GFP), we examined the effect of prolonged exposure to calorie restriction (CR) or rapamycin on hippocampal neural stem and progenitor cell proliferation in aging mice. We showed that CR increased the number of dividing cells in the dentate gyrus of female mice. The majority of these cells corresponded to nestin–GFP‐expressing neural stem or progenitor cells; however, this increased proliferative activity of stem and progenitor cells did not result in a significant increase in the number of doublecortin‐positive newborn neurons. Our results suggest that restricted calorie intake may increase the number of divisions that neural stem and progenitor cells undergo in the aging brain of females.